AMONGST THE FIELD, INTERESTS, AND PRODUCTIONS - Bruna Karolaynne Martins Amorim; Mayrhon José Abrantes Farias; Adriano Lopes de Souza (Formação Docente (Associação Nacional de Pós-Graduação e Pesquisa em Educação), 2023)
This study aims to map the themes addressed in graduation projects of the undergraduate Physical Education course of a higher education institution in the Tocantins state. It is a documental research of historical nature with a sample constituted of twenty-six papers developed by the two first entering classes. The results were organized based on three specific subfields: biodynamic, sociocultural, and pedagogical. We conclude that the needs and challenges of the graduation projects transcend the particularities of the school context, as demonstrated in the productions analyzed, being that course responsible, as well as all other undergraduate courses, for promoting the proper interlocutions between the academic and the professional fields.